Environment Actors Confronting a Post Climate-Related Disaster Scenario: A Feasibility Study of an Action-Based Intervention Aiming to Promote Climate Action - Areia, Neide P. (2021)
(1) A climate change awareness-action gap still prevails in our society, with individuals showing significant social inertia regarding environmental issues. The communication on climate change is pointed out as one of the causes of the social inertia; (2) Following an action-oriented transformation research, the main goal of this study was to ascertain the feasibility of an action-based communication intervention, based on the participants' exposure to a post climate-related disaster scenario. The feasibility of the action-based communication intervention was assessed in a focus group meeting, whose content was qualitatively analysed; (3) The results of this study demonstrate that action-based communication interventions are feasible to trigger an attitude transformation, catalysed by the experiential processing of climate change and by the affect arousal; (4) This study comes to contribute to a transformation of the climate change communication praxis, by highlighting the urgency to shift the for a new paradigm of communicating climate change, in which the affect and the experiential processing should account for conveying environment-related information in order to promote society's climate action.